Efek Pretreatment Ultrasonikasi Terhadap Hidrolisis Enzimatis Spirulina platensis Residue - Indriana Lestari; Heni Anggorowati; Faizah Hadi (Eksergi, 2021)
The development of renewable energy from microalgae sources is still being studied to overcome the world energy crisis, one of which is biodiesel from Spirulina platensis. However, the extraction process from Spirulina platensis to obtain oil leaving waste called Spirulina platensis residue (SPR). SPR still contains carbohydrates in the form of cellulose in cell walls and starch in plastids. Carbohydrates can be converted into bioethanol through the hydrolysis process. To optimize the enzymatic hydrolysis of carbohydrates, pretreatment is needed to break down the cell walls. One method of pretreatment is ultrasonication. This study aimed to determine the effect of ultrasonication pretreatment on enzymatic hydrolysis. Ultrasonication was carried out with time variations (15, 30, and 45 minutes) then continued hydrolysis at 40 oC for 8 hours using α-amylase and glucosidase (1: 1) enzymes. The results of hydrolysis in the form of reducing sugars were analyzed using the Nelson Somogyi method and obtained an optimal pretreatment time is 30 minutes with a reducing sugar concentration of 2.493,3 mg/L